Birding with benefits - Dubb, Sarah T. (Gallery Books, 2024)
"Newly-divorced, almost-empty-nester Celeste is finally seeking adventure and putting herself first, cliches be damned. So when a friend asks Celeste to "partner" with his buddy John for an event, Celeste throws herself into the role of his temporary girlfriend. But quiet cinnamon roll John isn't looking for love, just birds-he needs a partner for Tucson's biggest bird-watching contest if he's ever going to launch his own guiding business. By the time they untangle their crossed signals, they've become teammates ... and thanks to his meddling friends, a fake couple. Celeste can't tell a sparrow from a swallow, but John is a great teacher, and the hours they spend hiking in the Arizona wilderness feed Celeste's hunger for new adventures while giving John a chance to practice his dream job. As the two spend more time together, they end up watching more than just the birds, and their chemistry becomes undeniable. Since they're both committed to the single life, Celeste suggests a status upgrade: birders with benefits, just until the contest is done. But as the bird count goes up and their time together ticks down, John and Celeste will have to decide if their benefits can last a lifetime, or if this love affair is for the birds."--